2018
DOI: 10.1016/j.gene.2018.04.071
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in the communities of photosynthetic picoeukaryotes in Ofunato Bay as revealed by shotgun metagenomic sequencing

Abstract: Small photosynthetic eukaryotes play important roles in oceanic food webs in coastal regions. We investigated seasonal changes in the communities of photosynthetic picoeukaryotes (PPEs) of the class Mamiellophyceae, including the genera Bathycoccus, Micromonas and Ostreococcus, in Ofunato Bay, which is located in northeastern Japan and faces the Pacific Ocean. The abundances of PPEs were assessed over a period of one year in 2015 at three sampling stations, KSt. 1 (innermost bay area), KSt. 2 (middle bay area)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(28 reference statements)
1
4
0
Order By: Relevance
“…Ofunato Bay, winter is usually delayed due to the late arrival of the cold Oyashio Current from the north, and in our study, we found the seawater temperature in March 2015 to be lowest, ranging from 4.6 to 6.4˚C at the three sampling stations (Reza et al, 2018b;Rashid et al, 2018). Thus, May, August, November and March are spring, summer, autumn and winter, respectively, in the bay.…”
Section: Seasonal Changes Revealed By the Taxonomical Analysessupporting
confidence: 57%
“…Ofunato Bay, winter is usually delayed due to the late arrival of the cold Oyashio Current from the north, and in our study, we found the seawater temperature in March 2015 to be lowest, ranging from 4.6 to 6.4˚C at the three sampling stations (Reza et al, 2018b;Rashid et al, 2018). Thus, May, August, November and March are spring, summer, autumn and winter, respectively, in the bay.…”
Section: Seasonal Changes Revealed By the Taxonomical Analysessupporting
confidence: 57%
“…This reconstruction would have facilitated nutrient flow from the rivers and sewage near Ofunato Bay, which is an enclosed bay and would have retained the nutrients. The other possibility is the presence of nutrient uptake competitors in the bay, such as small eukaryotes, including photosynthetic picoeukaryotes 71 , which would have been trapped on the 5.0 or 0.8-µm filters.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in distribution and abundance are thought to be linked to alteration of physico-chemical factors of pond water. 32 Previous studies showed that species of Aphanizomenon, Oscillatoria, and Pseudanabaena from catfish aquaculture ponds produce 2-methylisoborneol. 33 Geosmin and 2-methylisoborneol are also responsible for many of the off-flavor episodes/problems in municipal drinking water systems worldwide.…”
Section: Discussionmentioning
confidence: 99%